2005
DOI: 10.1124/mol.105.012302
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Redox Protein Thioredoxin in Cytoprotective Mechanism Evoked by (-)-Deprenyl

Abstract: Through the inhibition of monoamine oxidase type B (MAO-B), (Ϫ)-deprenyl (selegiline) prevents the conversion of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) to the toxic metabolite 1-methyl-4-phenylpyridinium ion (MPP ϩ ) and also prevents the neurotoxicity in the dopaminergic neurons in animal models. Cumulative observations suggest that selegiline may also protect against MPP ϩ -induced neurotoxicity, possibly through the induction of pro-survival genes. We have observed that thioredoxin (Trx) mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Trx induction is known to be mediated by MAP kinase ERK (Andoh et al, 2005). Kong et al demonstrated that ERKs signal pathways are involved in SF-mediated up-regulation of Trx/TrxR/Nrf-2 expression in vivo (Kong et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Trx induction is known to be mediated by MAP kinase ERK (Andoh et al, 2005). Kong et al demonstrated that ERKs signal pathways are involved in SF-mediated up-regulation of Trx/TrxR/Nrf-2 expression in vivo (Kong et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Deprenyl and CGP-3466, drugs that protect neurons from stress-induced apoptosis [103] and slow the progression of Parkinson’s disease [104], bind to GAPDH [105] and inhibit both GAPDH S -nitrosylation and the GAPDH–Siah1 interaction in MPTP-treated mice [103]. Deprenyl also induces the expression of thioredoxin [106], a denitrosylase for GAPDH [107]. Conversely, BCNU (carmustine), a chemotherapeutic agent often used to treat brain and other cancers, increases SNO-GAPDH levels [108], providing a mechanism for sensitization of tumor cells to GAPDH-dependent death.…”
Section: Sno-gapdh and Cell Death – Therapeutic Implications In Neuromentioning
confidence: 99%
“…Finally, the thioredoxin (Trx) system deserves a mention because, in addition to its contribution to cellular defense against ROS, it is emerging as a key regulator of fundamental cellular processes (see sect. IIC), and the antidepressant deprenyl upregulated Trx in vitro (11).…”
Section: Discussionmentioning
confidence: 99%